Correlation of Observed-to-Expected MRI Fetal Lung Volume and Ultrasound Lung-to-Head Ratio at Different Gestational Times in Fetuses With Congenital Diaphragmatic Hernia - Kastenholz, Katrin E.; Weis, Meike; Hagelstein, Claudia; Weiss, Christel; Kehl, Sven; Schaible, Thomas; Neff, K. Wolfgang (American Journal of Roentgenology, 2016)
OBJECTIVE: The purpose of this study is to compare the observed-to-expected MRI fetal lung volume and the observed-to-expected ultrasound lung-to-head ratio intraindividually for prediction of survival, the need for extracorporeal membrane oxygenation (ECMO) therapy, and the development of chronic lung disease (CLD) at different times of gestation (< 28, 28-32, and > 32 weeks) in fetuses with congenital diaphragmatic hernia (CDH), and to analyze the intraindividual correlation of observed-to-expected MRI fetal lung volume and observed-to-expected ultrasound lung-to-head ratio. MATERIALS AND METHODS: Two hundred one fetuses were included in our study. Observed-to-expected MRI fetal lung volume and observed-to-expected ultrasound lung-to-head ratio were calculated for 270 MRI and ultrasound examinations performed within 72 hours of each other. The prognostic accuracy of observed-to-expected MRI fetal lung volume and observed-to-expected ultrasound lung-to-head ratio was assessed by performing ROC analysis. Correlation was determined using linear regression analysis. RESULTS: The results revealed statistically significant differences between the observed-to-expected MRI fetal lung volume and observed-to-expected ultrasound lung-to-head ratio for the prediction of survival, the need for ECMO therapy, and the development of CLD in fetuses with left-sided CDH (p ≤ 0.0444), with the highest prognostic accuracy for survival (AUC = 0.863). Observed-to-expected MRI fetal lung volume and observed-to-expected ultrasound lung-to-head ratio correlated statistically significantly (p < 0.0001) for left-sided CDH with correlation coefficients (r) of 0.71, 0.71, and 0.56 for early, intermediate, and late times of gestation, respectively. The correlation was not statistically significant at any time for right-sided CDH (p ≥ 0.3947; r ≤ 0.26). CONCLUSION: Observed-to-expected MRI fetal lung volume and observed-to-expected ultrasound lung-to-head ratio are valuable prognostic parameters for prenatal prediction of survival, the need for ECMO therapy, and the development of CLD in fetuses with left-sided CDH at all times of gestation. Observed-to-expected MRI fetal lung volume and observed-to-expected ultrasound lung-to-head ratio correlate statistically significantly for left-sided CDH, and the correlation is best before 32 weeks' gestation, but they do not correlate statistically significantly for right-sided CDH.
EVALuna2:33472